Study of risk factors associated with anaemia in children admitted to a subdistrict hospital - Patel, Uchit; Teckchandani, Rajesh; Barot, Nimesh; Parmar, Aditya; Kapadiya, Shirish (International Journal of Contemporary Pediatrics, 2026)
Background: Anaemia remains a significant public health problem among children, particularly in developing countries, leading to impaired growth, cognitive delay, and increased morbidity. Identifying the underlying risk factors is essential for effective prevention and management. Objectives were to study the prevalence and risk factors associated with Anaemia among children admitted to a subdistrict hospital. Methods: A cross-sectional observational study was conducted among 100 children admitted to the paediatric ward of a subdistrict hospital from April to September 2025. Detailed demographic data, dietary history, socioeconomic status (SES), clinical findings, and relevant laboratory investigations were recorded. Haemoglobin estimation was performed, and anaemia was classified as per WHO criteria. The association between potential risk factors and anaemia was analysed using appropriate statistical tests. Results: Overall, 65% of children were anaemic, with moderate anaemia observed in 55% and severe anaemia in 10%. Anaemia was significantly more prevalent among children with low birth weight (<2.5 kg) (81.0% vs 42.9%; OR=5.70; p<0.001). Children of mothers with low educational status had higher odds of anaemia (84.7% vs 36.6%; OR=9.63; p<0.001). Lower SES was also significantly associated with anaemia (81.1% vs 46.8%; OR=4.89; p<0.001). The prevalence and severity of anaemia increased with worsening nutritional status. Exclusive breastfeeding showed no statistically significant association with anaemia (p=0.23). Conclusions: Anaemia is highly prevalent among hospitalized under-five children and is strongly associated with low birth weight, poor maternal education, low SES, and malnutrition. Early screening and targeted nutritional and maternal interventions are essential to reduce the burden of childhood anaemia.